Do magnetic fields related to submarine power cables affect the functioning of a common bivalve?. (July 2022) - Jakubowska-Lehrmann, Magdalena; Białowąs, Marcin; Otremba, Zbigniew; Hallmann, Anna; Śliwińska-Wilczewska, Sylwia; Urban-Malinga, Barbara
Abstract: The aim of the study was to determine the effect of static magnetic field (SMF) and electromagnetic field (EMF), of values usually recorded near submarine cables, on the bioenergetics, oxidative stress, and neurotoxicity in the cockle Cerastoderma glaucum . Bivalves maintained a positive energy balance, but the filtration rate and energy available for individual production were significantly lower in SMF-exposed animals compared to the control treatment. No changes in the respiration were noted but ammonia excretion rate was significantly lower after exposure to EMF. Changes in the activities of antioxidant enzymes and the lipid peroxidation were not observed however, exposure to both fields resulted in increased protein carbonylation. After exposure to EMF a significant inhibition of acetylcholinesterase activity was observed. As the present study for the first time revealed the oxidative damage and neurotoxicity in marine invertebrate after exposure to artificial magnetic fields, the need for further research is highlighted. Graphical abstract: Image 1 Highlights: We assessed effects of static-SMF and alternating-EMF magnetic fields on C. glaucum . Filtration rate and scope for growth were lower in SMF-exposed bivalves. Ammonia excretion rate significantly decreased after exposure to EMF. Increased protein carbonylation was noted after exposure to both fields. Significant inhibition of AChE activity was observed after exposure to EMF.